DEVELOPMENT OF THE RADEN WALANGSUNGSANG HERITAGE TOURISM IN CIREBON GIRANG AND CHARACTER EDUCATION THROUGH ANTI-BULLYING SOCIALIZATION AT PRIMARY SCHOOL ONE OF CIREBON GIRANG AND RAUDHATUL ATHFAL CEMARA KINDERGARTEN - Ilham Ramadhan Prawasto; Melawati Melawati; Laela Susilawati; M. Alfito Jati; Sanusi Sanusi (Jurnal Abdisci, 2025)
This research was conducted during the Community Service Program (KKN) from February 13, 2025, to March 13, 2025. The study aims to develop educational tourism at the Raden Walangsungsang Heritage Site in Cirebon and integrate character education through an anti-bullying socialization program at SDN 1 Cirebon Girang and TK Ra Cemara. The research employs action research with a qualitative approach. The findings indicate that the development of educational tourism at the heritage site enhances students' understanding of local history and character values. Furthermore, the anti-bullying socialization program proves effective in increasing students' awareness of the negative impacts of bullying and the importance of mutual respect. Educational Tourism, Raden Walangsungsang Heritage Site, Character Education, Anti-Bullying